1997
DOI: 10.1089/hum.1997.8.15-1737
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Gene Transfer Reduces Intimal Thickening via Increased Production of Nitric Oxide in Carotid Arteries

Abstract: Thickening of the arterial intima and smooth muscle cell (SMC) proliferation remain major problems after vascular surgery and other types of vascular manipulations. We studied the effect of endothelial cell (EC)-specific vascular endothelial growth factor (VEGF) gene transfer on the thickening of the intima using a silicone collar inserted around carotid arteries that acted both as the agent that caused intimal SMC growth and as a reservoir for the transfected gene. The model preserved EC integrity and permitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
146
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(153 citation statements)
references
References 35 publications
5
146
0
2
Order By: Relevance
“…13 Adventitial delivery of plasmids and oligonucleotides has also been reported in a number of other applications. 8,10,22 In human atherosclerotic arteries, 5% transfection efficiency via the intravascular route has been recently achieved with adenoviruses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 Adventitial delivery of plasmids and oligonucleotides has also been reported in a number of other applications. 8,10,22 In human atherosclerotic arteries, 5% transfection efficiency via the intravascular route has been recently achieved with adenoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,23 Furthermore, human lesions are frequently rich in connective tissue and contain only a limited number of transfectable cells in the intimal part of the lesion. To circumvent these problems adventitial gene delivery can be performed with a silastic or biodegradable collar, 13 biodegradable gel, 5 or direct injection into adventitia. 22 It is concluded that local gene transfer with cationic polymer-plasmid complexes provides an efficient way for the treatment of arterial diseases during vascular surgery, such as prosthesis and anastomosis operations and by-pass surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also a cytoprotective and anti-apoptotic factor leading to the inhibition of neointimal growth during vascular damage, and inducing angiogenesis especially in ischaemic tissues. [1][2][3][4][5][6][7] Therapeutic angiogenesis and inhibition of restenosis were the first targets of VEGF gene therapy. 2,5,7,8 The VEGF family consists of several members: VEGF (also called VEGF-A), VEGF-B, VEGF-C, VEGF-D, VEGF-E, VEGF-F and placental growth factor.…”
Section: Introductionmentioning
confidence: 99%